Contribution of microglia/macrophage to the pathogenesis of TMEV infection in the central nervous system - Zhang, Qianye; Sun, Wei; Zheng, Mingxiao; Zhang, Ning (Frontiers in Microbiology, 2024)
The infection of the central nervous system (CNS) with neurotropic viruses induces neuroinflammation and an immune response, which is associated with the development of neuroinflammatory and neurodegenerative diseases, including multiple sclerosis (MS). The activation of both innate and adaptive immune responses, involving microglia, macrophages, and T and B cells, while required for efficient viral control within the CNS, is also associated with neuropathology. Under pathological events, such as CNS viral infection, microglia/macrophage undergo a reactive response, leading to the infiltration of immune cells from the periphery into the brain, disrupting CNS homeostasis and contributing to the pathogenesis of disease. The Theiler's murine encephalomyelitis virus (TMEV)-induced demyelination disease (TMEV-IDD), which serves as a mouse model of MS. This murine model made significant contributions to our understanding of the pathophysiology of MS following subsequent to infection.Microglia/macrophages could be activated into two different states, classic activated state (M1 state) and alternative activated state (M2 state) during TMEV infection. M1 possesses the capacity to initiate inflammatory response and secretes pro-inflammatory cytokines, and M2-liked microglia/macrophages are anti-inflammatory characterized by the secretion of anti-inflammatory cytokines. This review aims to discuss the roles of microglia/macrophages M1/M2-liked polarization during TMEV infection, and explore the potential therapeutic effect of balancing M1/M2-liked polarization of microglia/macrophages on MS.